2015
DOI: 10.1152/japplphysiol.00934.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high flow clears anatomical dead space in upper airway models

Abstract: Recent studies showed that nasal high flow (NHF) with or without supplemental oxygen can assist ventilation of patients with chronic respiratory and sleep disorders. The hypothesis of this study was to test whether NHF can clear dead space in two different models of the upper nasal airways. The first was a simple tube model consisting of a nozzle to simulate the nasal valve area, connected to a cylindrical tube to simulate the nasal cavity. The second was a more complex anatomically representative upper airway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
164
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(178 citation statements)
references
References 25 publications
8
164
1
5
Order By: Relevance
“…When a two-hole cannula fitting in both nostrils was used, its effect on the oxygenation was more pronounced, and when a single-hole cannula fitting in a single nostril was used, its effect on oxygen elimination was more pronounced (12). In a similar animal study, Möller et al (13) randomly compared continuous airway pressures (CPAP, 2-6 cm H 2 O), HFNO in which only a small leak was allowed, and HFNO in which a larger leak was allowed in 13 newborn and spontaneously breathing piglets with lung perforations. It has been found that the tracheal pressures of CPAP and HFNO are comparable.…”
Section: A the Clearance Of Nasopharyngeal Dead Spacementioning
confidence: 90%
“…When a two-hole cannula fitting in both nostrils was used, its effect on the oxygenation was more pronounced, and when a single-hole cannula fitting in a single nostril was used, its effect on oxygen elimination was more pronounced (12). In a similar animal study, Möller et al (13) randomly compared continuous airway pressures (CPAP, 2-6 cm H 2 O), HFNO in which only a small leak was allowed, and HFNO in which a larger leak was allowed in 13 newborn and spontaneously breathing piglets with lung perforations. It has been found that the tracheal pressures of CPAP and HFNO are comparable.…”
Section: A the Clearance Of Nasopharyngeal Dead Spacementioning
confidence: 90%
“…Reduced dead space ventilation and thus reduced rebreathing of expired air in a flow-dependent manner is another benefit that is attributed to high gas flow that is delivered by this device, as demonstrated in studies using upper airway models as well as on healthy volunteers [11,12]. The mechanism differs between sleep and awake states, because of different ventilatory responses to NHF in each state.…”
Section: Mechanisms Of Actionmentioning
confidence: 95%
“…Even without lung expansion, oxygen diffusion from the alveoli to the capillaries decreases alveolar pressure, and by increasing pharyngeal oxygen content a flow of air is generated from the pharynx to the distal airway, which is called apnoeic oxygenation [61]. High flow rates with NHF create a great oxygen reservoir in nasopharyngeal area, which together with carbon dioxide elimination by flushing of the dead space [11,12] and the generated CPAP [3][4][5][6][7][8] make NHF a promising oxygenation device in the peri-intubation period, which maintains oxygenation without a rapid and dangerous rise in carbon dioxide concentration [62].…”
Section: No Benefitmentioning
confidence: 99%
“…Bis heute konnten mehrfach die Vorteile der NHF-Sauersto therapie im Vergleich zur konventionellen Sauersto therapie [1] oder nicht invasiven Ventilationstherapie [2] bei Patienten mit hypoxämischer Atmungsinsu zienz gezeigt werden. Die positiven E ekte beruhen teilweise darauf, dass eine höhere Sauersto konzentration appliziert werden kann, auf einer verbesserten mukoziliären Clearance durch die Anwärmung der Atemluft [3] und auf dem Aufbau eines positiven Atemwegsdruckes bei gleichzeitiger Senkung des Totraums [4] durch den hohen Gasuss. Positive E ekte auf das hyperkapnische Atmungsversagen konnten jedoch bis jetzt noch nicht gezeigt werden, wobei aktuell die Verö entlichung mehrerer -teils abgeschlossener -Studien zur Klärung dieser Frage bevorsteht.…”
Section: High-flow-sauerstoff Als Option Bei Maskenintoleranzunclassified